Xanthogranulomatous pyelonephritis: a case with rare adhesion to pancreas. Issue 1 (May 2018) - Devrim, Tuba; Atasoy, Pınar; Tuğlu, Devrim
Abstract Xanthogranulomatous pyelonephritis (XGP) is a rare benign condition with unknown aetiology and chronic infection of kidney. Commonly, most cases are related with urinary tract obstruction, nephrolithiasis, infection, diabetes, and/or immune compromise. XGP is associated with destruction of the renal parenchyma and granulomatous inflammation with foamy lipid-laden macrophages resulting from obstructive uropathy. It closely mimics a malignancy, exhibiting local tissue invasion and destruction. Adjacent organs especially duodenum as well as very rarely pancreas or spleen may be involved. Additionally, XGP is known as notorious for fistulisations, such as pyelocutaneous and ureterocutaneous fistulae, which have been reported as well described. XGP may be indistinguishable from renal cell carcinoma by radiographic and clinic consultation so it must be diagnosed based on the histopathologic examinations. Furthermore, macroscopic appearance of XGP is a mass of yellow tissue with focal haemorrhage besides necrosis and in this regard, it grossly resembles renal cell carcinoma. Here, we report the case of a 32-year-old female, preoperatively diagnosed as malignancy by clinical examination. Our further pathological evaluations revealed very rarely adhesion of XGP to pancreas tissue.